Potential Role of Chronic Physical Exercise as a Treatment in the Development of Vitiligo - de França, Elias; dos Santos, Ronaldo V. T.; Baptista, Liliana C.; Da Silva, Marco A. R.; Fukushima, André R.; Hirota, Vinícius B.; Martins, Raul A.; Caperuto, Erico C. (Frontiers in Physiology, 2022)
Vitiligo is an autoimmune disease characterized by progressive skin depigmentation and the appearance of white patches throughout the body caused by significant apoptosis of epidermal melanocytes. Despite not causing any physical pain, vitiligo can originate several psychosocial disorders, drastically reducing patients’ quality of life. Emerging evidence has shown that vitiligo is associated with several genetic polymorphisms related to auto-reactivity from the immune system to melanocytes. Melanocytes from vitiligo patients suffer from excess reactive oxygen species produced by defective mitochondria besides a poor endogenous antioxidant system (EAS). This redox imbalance results in dramatic melanocyte oxidative stress (OS), causing significant damage in proteins, lipid membranes, and DNA. The damaged melanocytes secret damage-associated molecular pattern, inducing and increasing inflammatory gene expression response that ultimately leads to melanocytes apoptosis. Vitiligo severity has been also associated with increasing the prevalence and incidence of metabolic syndrome (MetS) or associated disorders such as insulin resistance and hypercholesterolemia. Thus, suggesting that in genetically predisposed individuals, the environmental context that triggers MetS (i.e., sedentary lifestyle) may also be an important trigger for the development and severity of vitiligo disease. This paper will discuss the relationship between the immune system and epidermal melanocytes and their interplay with the redox system. Based on state-of-the-art evidence from the vitiligo research, physical exercise (PE) immunology, and redox system literature, we will also propose chronic PE as a potential therapeutic strategy to treat and prevent vitiligo disease progression. We will present evidence that chronic PE can change the balance of inflammatory to an anti-inflammatory state, improve both EAS and the mitochondrial structure and function (resulting in the decrease of OS). Finally, we will highlight clinically relevant markers that can be analyzed in a new research avenue to test the potential applicability of chronic PE in vitiligo disease.